Why do ICDPs fail? The relationship between subsistence farming, poaching and eco- tourism in wildlife and habitat conservation - Ralph Winkler (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
In this paper we investigate the reasons why integrated conservation and development projects (ICDPs) fail to achieve their conservation goals. We develop a bio-economic model of open access land and wildlife exploitation, which is consistent with many farming and hunting societies living in close proximity to forest reserves in developing countries. We show that the ICDP creates incentives to conserve habitat and wildlife, but, in general, the socially optimal level of conservation cannot be achieved, because of externalities among the local communities. We show how a social planner can achieve the socially optimal levels of habitat and wildlife by a more encompassing tax/subsidy regime.
Keywords: Q56; O13; H23; 330; bio-economic modelling; competing land-use; ecotourism; integrated conservation and development projects; poaching; wildlife and habitat conservation; Schutzgebiet; Wildtierschutz; Ökotourismus; Landnutzung; Externer Effekt; Modellierung; Bioökonomik; Theorie